DETERMINING THE EFFECT OF NON-MONETARY FACTORS ON INFLATION IN UZBEKISTAN (Journal of Universal Science Research, 2023)
Inflation level of the economy main from the indicators one is considered Him in moderation holding stand up state , that's it including central of the bank task is considered In the article non-monetary of factors to inflation effect discussion will be done .